Keanggotaan Notaris Dalam Organisasi Ikatan Notaris Indonesia: Mandatory Vs Voluntary - Rienda Cintya Dewi, Ida Ayu Kade (Acta Comitas : Jurnal Hukum Kenotariatan, 2018)
There is a vague norm in the UUJN regarding the word "mandate" which is regulated by Article 16 paragraph (1) letter a of the UUJN if it is associated with the obligation of membership of a Notary as a member of INI organization. Based on the obscurity of these norms, the formulation of the problem is formulated, namely: (1) How is the regulation of the obligations of Notary Membership in INI according to the UUJN? (2) What is the sanction if a Notary is not a member in INI? The purpose of this writing is generally related to notary fields in legal studies relating to membership of notaries in INI. Based on these general objectives, the specific purpose is to find out and understand how to regulate the obligations for membership of Notaries in INI according to the UUJN; and to review and analyze how sanctions are if a Notary is not a member of INI. Normative legal research is used in this study which is carried out by a conceptual approach (Conceptual Approach) and the statutory approach (The Statute Approach). Primary, secondary and tertiary legal materials are used in this study as a source of legal material with legal material collection techniques using a single method namely literature study in normative legal research that is applied with the use of snow ball methods. This study provides results in the form of: (1) Notaries must become members of INI organization, as contained in the UUJN that notaries are obliged to act trustworthy. The act of trust is interpreted as something entrusted to the unity of people, which in this case is INI. Arrangements regarding notary membership obligations in INI are contained in the UUJN, the Notary Code of Ethics and the Constitutional Court Decision; and (2) Notaries who do not participate in INI membership receive sanctions in the form of written warnings, temporary terminations, respectful terminations, or dishonorable dismissals.